Smart City and Images: The Use of Image Hashtags to Get Insights on Citizens - De Michele, Roberta; Furini, Marco (Lecture notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2018)
The knowledge of citizens’ interests and problems is crucial for the smart management of a city. Up to few years ago, the employment of opinion agencies was mandatory to get this knowledge, but since this process is cost and time consuming, many studies are beginning to exploit social media contents to understand citizens. In particular, the attention is usually focused on textual data, and only few studies consider multimedia contents. In this paper, we investigate whether it is possible to know citizens’ interests and problems by using images published in the Instagram platform. In particular, we propose a method that analyzes and measures the importance of hashtags associated to images. The experimental evaluation shows that images could be an important source of information to understand citizens.